Experimental and numerical study on the behaviour of CFDST columns subjected to close-in blast loading. (15th April 2019) - Li, Minghong; Zong, Zhouhong; Hao, Hong; Zhang, Xihong; Lin, Jin; Xie, Guanyu
Highlights: Field tests were conducted on large scale CFDST columns subjected to close-in explosion. Numerical models were developed and verified against experimental results. Damage mechanisms of CFDST columns under close-in blast loading were investigated. Energy absorption mechanisms of CFDST columns under close-in explosion were analyzed. Effects of explosive charge setups and axial loads were assessed and discussed. Abstract: The dynamic behaviour of concrete-filled double-skin steel tube (CFDST) columns under close-in blast loading was investigated using experimental and numerical approaches in the present study. Field test results on three large scale CFDST column specimens subjected to different blast loading conditions were presented. High-fidelity physics-based numerical models were developed utilizing the Arbitrary-Lagrangian-Eulerian (ALE) formulation coupled with Fluid-Structure Interaction (FSI) algorithm available in the nonlinear dynamic analysis program LS-DYNA. The numerical models were verified with the experiment results and were then used to investigate the dynamic response, damage mechanism and energy absorption capacity of CFDST columns subjected to close-in explosions. The results indicated that the typical failure pattern of CFDST columns under close-in blast loading is dominated by localized denting of the cross-section directly facing the explosion with minor global deformation of the column. The concrete core suffers severe damage while the steel tubes remain almost undamaged except in a limited region in the vicinity of the detonation. The energy absorbed by each part of the CFDST columns demonstrates that the severe plastic damage of concrete core plays a significant role in the energy absorption mechanism of CFDST columns under blast loading from close-in explosion. The primary function of the steel tubes is to provide confinement to the concrete core therefore prevent concrete spall damage. In addition, the influence of explosive charge setups and level of axial loads on the structural response and damage was assessed and discussed.